The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/access.2021.3128999
|View full text |Cite
|
Sign up to set email alerts
|

Robust Coordination Scheme for Microgrids Protection Based on the Rate of Change of Voltage

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…It is necessary to state that in [116] it is concluded that ROCOV relays are superior in selectiveness and reliability than the conventional current and voltage protection devices. Finally, [117] proposes a coordination scheme for microgrids based on the ROCOV measurement.…”
Section: ) Rate Of Change Of Voltage (Rocov)mentioning
confidence: 99%
“…It is necessary to state that in [116] it is concluded that ROCOV relays are superior in selectiveness and reliability than the conventional current and voltage protection devices. Finally, [117] proposes a coordination scheme for microgrids based on the ROCOV measurement.…”
Section: ) Rate Of Change Of Voltage (Rocov)mentioning
confidence: 99%
“…The microgrid can solve this overload issue using two Pmax controllers [59,60]. The key concept to this is that, once Inv1 reaches Pmax, the controller will be activated to reduce the frequency of Inv1 rapidly, and by reducing the frequency, we can change the phase angle between these two inverters, so this can redistribute the power flow between the two inverters.…”
Section: The Survival Of Autonomous Microgrids During Overload Eventsmentioning
confidence: 99%
“…Article [157], presents the stochastic-based energy management system and protection method for the reliable operation of the microgrid. The rate of change of voltage-based protection scheme and coordination scheme is introduced for the protection of the microgrid [158]. In [159], a new protection scheme is proposed for the internal faults of the multi-microgrids.…”
Section: Critical Analysis and Solution Approachesmentioning
confidence: 99%